Determinan Kelengkapan Imunisasi Campak pada Anak Balita di Kelurahan Naikolan - Mariana Paulina Putri Billa; Muntasir Muntasir; Tadeus Andreas Lada Regaletha (FORIKES, 2023)
Completeness of measles immunization is effective in preventing transmission of measles so that its coverage needs to be increased. The purpose of this study was to analyze factors related to the status of completeness of measles immunization in children under five in Naikolan Village. This type of research was a quantitative study with a cross-sectional design. The research sample was mothers with toddlers aged 24-35 months who live in the Naikolan Village area, with a sample size of 54 people, who were selected by purposive sampling technique. The variables studied included the mother's level of knowledge, mother's occupation, income, husband's support, health worker support, and measles immunization completeness status. Bivariate analysis was performed using the Chi-square test or Fisher's exact test. The results showed that the p-value for each factor was mother's level of knowledge = 0.484, mother's occupation = 0.176, income = 1.000, and husband's support = 0.413, support from health workers = 0.006. Furthermore, it was concluded that the factor associated with the completeness status of measles immunization was the support of health workers. It is hoped that health workers at the Sikumana Health Center and Naikolan Pustu will improve the quality of services, especially in providing service support for mothers who have children under five to complete the status of measles immunization in children under five in Naikolan Village.Keywords: immunization; measles; toddler; health workers ABSTRAK Kelengkapan imunisasi campak efektif untuk mencegah penularan penyakit campak sehingga perlu ditingkatkan cakupannya. Tujuan penelitian ini adalah untuk menganalisis faktor yang berhubungan dengan status kelengkapan imunisasi campak pada anak balita di Kelurahan Naikolan. Jenis penelitian ini adalah studi kuantitatif dengan desain cross-sectional. Sampel penelitian adalah ibu yang mempunyai anak balita berusia 24-35 bulan yang berdomisili di wilayah Kelurahan Naikolan, dengan ukuran sampel 54 orang, yang dipilih dengan teknik purposive sampling. Variabel yang diteliti meliputi tingkat pengetahuan ibu, pekerjaan ibu, pendapatan, dukungan suami, dukungan petugas kesehatan, dan status kelengkapan imunisasi campak. Analisis bivariat dilakukan menggunakan uji Chi-square atau Fisher’s exact test. Hasil penelitian menunjukkan bahwa nilai p untuk masing-masing faktor adalah tingkat pengetahuan ibu = 0,484, pekerjaan ibu = 0,176, pendapatan = 1,000, dan dukungan suami = 0,413, dukungan petugas kesehatan = 0,006. Selanjutnya disimpulkan bahwa faktor yang berhubungan dengan status kelengkapan imunisasi campak adalah dukungan petugas kesehatan. Diharapkan petugas kesehatan di Puskesmas Sikumana dan Pustu Naikolan meningkatkan kualitas pelayanan khususnya dalam memberikan dukungan pelayanan bagi ibu yang memiliki anak balita untuk kelengkapan status imunisasi campak pada anak balita di Kelurahan Naikolan.Kata kunci: imunisasi; campak; balita; petugas kesehatan